Reducing Earnings Management With Existence of Women on Board? A Literatur Review - Zalfa Shafira Qatrunnada (Postgraduate Program Merdeka University, 2024)
This study aims to review a number of literature regarding the effectiveness of the role of gender diversity or the presence of women on the company's board of directors in reducing earnings management practices. This literature review reviews a number of articles with relevant themes, namely earnings management and gender diversity published in the 2015-2023 period. The results show that the existence of female directors reduces earnings management practices, especially for companies with at least three female directors, female directors with financial backgrounds and outside positions. On the other side, reducing earnings management does not affected by gender diversity due to the lack of women proportion in the board of directors structure.DOI: https://doi.org/10.26905/afr.v7i1.10450